L’immaginario perverso delle guerre - Palumbo, Fabio Domenico (Mechane, 2023)
In his essay Il gesto di Caino, Massimo Recalcati highlights the ubiquitous link between narcissism, fascination and violence. The fratricidal murder of Abel arises from the perception that the ideal image of the Other cannot be captured by the Ego. Hallucinatory violence, as shown by Franco Fornari in his crucial Psicoanalisi della guerra, aims to saturate the hole opened in the plot of the Real by the unavoidable presence of otherness, which forces us to cope with the limits of our claim to govern our lives. Furthermore, what we intend to explore in this work are the disturbing chances offered by technological development, not only to amplify the acephalous nature of the death drive through brutal technologies such as the atomic weapon – where the paranoid effort to subjugate the Other coincides with the loss of any form of control over one’s own destructive power –, but also to create a perverse union between the subjugation of the enemy through technological devices and the imaginary “capture” of the victim through images intended to convey the “scene” of war. Taking up some concepts expressed within L’immagine carnefice, a collective volume dedicated to the relationship between violence and the imaginary (photographic, serial, cinematographic), here we try to follow the perverse trait of the aesthetic dimension at work in contemporary declinations of war violence. It is in this short-circuit between hyper-visibility and invisibility that war reveals the perverse vocation of the death drive.